Evaluative Literature Review Writing by Novice Academic Writers: Enhancing Knowledge and Awareness - Aksakallı Canan; Yağız Oktay; Bakırtaş Şennur; Ötügen Rabia (Darnioji daugiakalbystė)
An evaluative and critical literature review in scholarly writing, which plays an important part in a scientific report, illustrates how the existing studies contributed to the relevant field and enables researchers to identify the gaps or niches that their research can fill. However, writing evaluative and critical literature reviews is challenging for non-native speakers of English (NNES). Literature reviews are frequently descriptive summaries of previous research. Beyond simply summarizing source materials, NNES academic writers, inclusive of novice academic writers, should be aware of the ways of developing evaluative and critical literature reviews by making connections between the research findings and interpretations of published studies, showing their inconsistencies, and identifying their strengths and weaknesses. This study aimed to explore NNES doctoral students’ knowledge and awareness of evaluative literature review writing and enhance their knowledge with an implementation focusing on the conventions and norms of literature review writing. The study adopted an embedded quasi-experimental design. 20 Turkish doctoral students from different educational science departments participated in the study. The quantitative analysis of the literature review tasks submitted by the participants during the pre- and post-intervention phases and the themes gathered from the semi-structured interviews revealed that NNES students had several challenges when they wrote literature reviews. The supportive implementation, which aimed at evaluative and critical literature review writing, positively affected students’ skills, increasing their awareness about the characteristics of effective literature reviews and improving their evaluation and critical thinking skills. The results also offered insights into graduate students’ strengths and weaknesses in evaluative and critical literature review writing.